Dialog Bunyi: Reinterpreting Uroh Rapai as a Manifestation of Social Piety in Musical Composition - Angga Eka Karina; Dwindy Putri Cufara; Toza Darlija; Riqi Anugerah (Universitas Negeri Medan, 2025)
This research aims to investigate the uroh rapai tradition in North Aceh, focusing on rapai pase, a unique form of Acehnese membranophone that is performed in competitive settings. The study emphasizes the philosophical and social dimensions of uroh rapai by interpreting it as a manifestation of social piety. Employing a practice-led approach, where the creative process itself becomes the core of inquiry, the study integrates three fundamental principles of piety: habluminallah (human relationship with God), habluminannas (human relationship with others), and habluminalalam (human relationship with nature). Data were collected through literature review, direct observation of uroh performances, and in-depth interviews with syeh rapai and players. These insights were then transformed into an experimental musical composition entitled Dialog Bunyi. The result is in a form of composition, structured into three segments; first, natural soundscapes symbolizing ecological harmony, second, instrumental interaction as a metaphor of social solidarity; and third, rapai rhythms and devotional chanting as an expression of spiritual devotion. Its premiere performance demonstrated how traditional art can be recontextualized into contemporary works, rooted in Acehnese identity. The research contributes a new methodological and pedagogical model for tradition-based music studies, offering a way to preserve and creatively reinterpret cultural heritage.